Seed Biology Updates - Jimenez-Lopez, Jose C. (IntechOpen, 2022)
Abiotic stresses negatively affect crop production and thus threaten global food security. To confront this challenge, it is important to understand the physiological processes and functional cues of seeds, particularly in the field of seed development (seed filling), and its influence on seed dormancy and germination. This book presents a comprehensive overview of seed physiology and the effects of stressors such as salinity, drought, and high temperature. It also discusses the genetic mechanisms and biochemical and physiological cues that govern seed filling, seed development features under stress environments, seed dormancy and germination, and agronomic management to help crops develop resilience to climate change.